Sorry if this is messy but I hope it helps you
Answer:
(-8 , 3)
Step-by-step explanation:
(x1 , y1) (x2 , y2) = (-10 , -1) (-6 , 7)
,
-6 is going to be my x1 and -10 my y1
7 is going to be my x2 and -1 my y2
(-8 , 3)
Answer:
Step-by-step explanation:
A linear equation in two variables doesn't involve any power higher than one for either variable. It has the general form Ax + By + C = 0, where A, B and C are constants. ... A quadratic equation, on the other hand, involves one of the variables raised to the second power. It has the general form y = ax2 + bx + c
Answer:
![g^-^1(x)=-8](https://tex.z-dn.net/?f=g%5E-%5E1%28x%29%3D-8)
![h^-^1(x)=\frac{x-4}{3}](https://tex.z-dn.net/?f=h%5E-%5E1%28x%29%3D%5Cfrac%7Bx-4%7D%7B3%7D)
![(h^-^1 \ o\ h)(-3)=-3](https://tex.z-dn.net/?f=%28h%5E-%5E1%20%5C%20o%5C%20h%29%28-3%29%3D-3)
Step-by-step explanation:
When given the following functions,
![g=[(-2,-7),(4,6),(6,-8),(7,4)]](https://tex.z-dn.net/?f=g%3D%5B%28-2%2C-7%29%2C%284%2C6%29%2C%286%2C-8%29%2C%287%2C4%29%5D)
![h(x)=3x+4](https://tex.z-dn.net/?f=h%28x%29%3D3x%2B4)
One is asked to find the following,
1. Question 1
![g^-^1(4)](https://tex.z-dn.net/?f=g%5E-%5E1%284%29)
When finding the inverse of a function that is composed of defined points, one substitutes the input given into the function, then finds the output. After doing so, one must substitute the output into the function, and find its output. Thus, finding the inverse of the given input;
![g^-^1(4)](https://tex.z-dn.net/?f=g%5E-%5E1%284%29)
![g(4)=6\\g(6)=-8\\g^-^1(4)=-8](https://tex.z-dn.net/?f=g%284%29%3D6%5C%5Cg%286%29%3D-8%5C%5Cg%5E-%5E1%284%29%3D-8)
2. Question 2
![h^-^1(x)](https://tex.z-dn.net/?f=h%5E-%5E1%28x%29)
Finding the inverse of a continuous function is essentially finding the opposite of the function. An easy trick to do so is to treat the evaluator (h(x)) like another variable. Solve the equation for (x) in terms of (h(x)). Then rewrite the equation in inverse function notation,
![h(x)=3x+4\\\\h(x)-4=3x\\\\\frac{h(x)-4}{3}=x\\\\\frac{x-4}{3}=h^-^1(x)](https://tex.z-dn.net/?f=h%28x%29%3D3x%2B4%5C%5C%5C%5Ch%28x%29-4%3D3x%5C%5C%5C%5C%5Cfrac%7Bh%28x%29-4%7D%7B3%7D%3Dx%5C%5C%5C%5C%5Cfrac%7Bx-4%7D%7B3%7D%3Dh%5E-%5E1%28x%29)
![h^-^1(x)=\frac{x-4}{3}](https://tex.z-dn.net/?f=h%5E-%5E1%28x%29%3D%5Cfrac%7Bx-4%7D%7B3%7D)
3. Question 3
![(h^-^1 \ o\ h)(-3)](https://tex.z-dn.net/?f=%28h%5E-%5E1%20%5C%20o%5C%20h%29%28-3%29)
This question essentially asks one to find the composition of the function. In essence, substitute function (h) into function (
) and simplify. Then substitute (-3) into the result.
![h^-^1\ o\ h](https://tex.z-dn.net/?f=h%5E-%5E1%5C%20o%5C%20h)
![\frac{(3x+4)-4}{3}\\\\=\frac{3x+4-4}{3}\\\\=\frac{3x}{3}\\\\=x](https://tex.z-dn.net/?f=%5Cfrac%7B%283x%2B4%29-4%7D%7B3%7D%5C%5C%5C%5C%3D%5Cfrac%7B3x%2B4-4%7D%7B3%7D%5C%5C%5C%5C%3D%5Cfrac%7B3x%7D%7B3%7D%5C%5C%5C%5C%3Dx)
Now substitute (-3) in place of (x),
![=-3](https://tex.z-dn.net/?f=%3D-3)
Answer:
50,000
Step-by-step explanation: